The Effect of Recruitment, Selection, and Training on Employee Performance at PT. BPR Khrisna Darma Adipala - Ni Putu Ayu Sintya Saraswati; Ni Made Satya Utami; Ni Made Dirma Setia Dewi (Institut Bisnis dan Teknologi Pelita Indonesia, 2025)
With a wide range of skills and abilities at work, employee success is one of the most important things that companies need to think about in order to get the best results. The study's goal is to find out how hiring, teaching, and choosing workers at PT. BPR Khrisna Darma Adipala affect how well they do their jobs. The research was carried out at PT. BPR Khrisna Darma Adipala. One hundred and forty people who worked at PT. BPR Khrisna Darma Adipala took part in this study. To find the sample, the saturation sampling method was used. The information for this study came from polls, conversations, notes, and written records. To do multiple linear regression analysis on the data in this study, SPSS version 25.0 is used. The study discovered that both hiring and selection have a good and significant effect on how well employees do their jobs at PT. BPR Khrisna Darma Adipala. Training has a big and good effect on how well employees do their jobs at PT. BPR Khrisna Darma Adipala.